Ventilatory and pulmonary vascular response to hypoxia and susceptibility to high altitude pulmonary oedema - Hohenhaus, Elke; Paul, A.; McCullough, R. E.; Kücherer, Helmut; Bärtsch, Peter (The European respiratory journal, 1995)
Reduced tolerance to high altitude may be associated with a low ventilatory and an increased pulmonary vascular response to hypoxia. We therefore, examined whether individuals susceptible to acute mountain sickness (AMS) or high altitude pulmonary oedema (HAPE) could be identified by noninvasive measurements of these parameters at low altitude. Ventilatory response to hypoxia (HVR) and hypercapnia (HCVR) at rest and during exercise, as well as hypoxic pulmonary vascular response (HPVR) at rest, were examined in 30 mountaineers whose susceptibility was known from previous identical exposures to high altitude. Isocapnic HVR expressed as difference in minute ventilation related to difference in arterial oxygen saturation (delta V'E/ delta Sa,O2) (L.min-1/%) was significantly lower in subjects susceptible to HAPE (mean +/- SEM 0.8 +/- 0.1; n = 10) compared to nonsusceptible controls (1.5 +/- 0.2; n = 10), but was not significantly different from subjects susceptible to AMS (1.2 +/- 0.2; n = 10). Hypercapnic ventilatory response was not significantly different between the three groups. Discrimination between groups could not be improved by measurements of HVR during exercise (50% maximum oxygen consumption (V'O2,max)), or by assessing ventilation and oxygen saturation during a 15 min steady-state exercise (35% V'O2,max) at fractional inspiratory oxygen (FI,O2) of 0.14. Pulmonary artery pressure (Ppa) estimated by Doppler measurements of tricuspid valve pressure at an FI,O2 of 0.21 and 0.12 (10 min) did not lead to a further discrimination between subjects susceptible to HAPE and AMS with the exception of three subjects susceptible to HAPE who showed an exaggerated HPVR. It is concluded that a low ventilatory response to hypoxia is associated with an increased risk for high altitude pulmonary oedema, whilst susceptibility to acute mountain sickness may be associated with a high or low ventilatory response to hypoxia. A reliable discrimination between subjects susceptible to high altitude pulmonary oedema and acute mountain sickness with a low ventilatory response to hypoxia is not possible by Doppler echocardiographic estimations of hypoxic pulmonary vascular response.